2021
DOI: 10.1371/journal.pone.0255946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on skeletal muscle contractile performance in male and female mice

Abstract: Background Acute and chronic alcohol use can cause skeletal muscle myopathy in concert with impairments in skeletal muscle strength, function and fatigue resistance. However, the fundamental contractile deficits induced in the presence of alcohol versus those observed in the recovery period following the clearance of alcohol have not yet been characterized nor is it known whether sex influences these outcomes. Methods Male and female mice received an intraperitoneal injection of either saline (Control) or et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…This study found no significant difference in the basic electrophysiological properties of male and female rat MNs. These results were unexpected, given the numerous studies that indicate considerable sexual dimorphism in muscle mass, morphology, motor innervation, fibre biochemical composition and motor unit contractility (Celichowski & Drzymała‐Celichowska, 2007; Drzymała‐Celichowska & Krutki, 2015; Eason et al, 2000; English et al, 1999; English & Widmer, 2003; Mierzejewska‐Krzyżowska et al, 2011), which appear to be essential for the obvious differences in motor performance observed between male and female animals (Laudato et al, 2021; Mortreux et al, 2021) and humans (Hicks et al, 2001; Roberts et al, 2020). Differences between sexes in the electrophysiological properties of MNs would have a significant impact on the recruitment of motor units and the rate of force development during contractions.…”
Section: Discussionmentioning
confidence: 99%
“…This study found no significant difference in the basic electrophysiological properties of male and female rat MNs. These results were unexpected, given the numerous studies that indicate considerable sexual dimorphism in muscle mass, morphology, motor innervation, fibre biochemical composition and motor unit contractility (Celichowski & Drzymała‐Celichowska, 2007; Drzymała‐Celichowska & Krutki, 2015; Eason et al, 2000; English et al, 1999; English & Widmer, 2003; Mierzejewska‐Krzyżowska et al, 2011), which appear to be essential for the obvious differences in motor performance observed between male and female animals (Laudato et al, 2021; Mortreux et al, 2021) and humans (Hicks et al, 2001; Roberts et al, 2020). Differences between sexes in the electrophysiological properties of MNs would have a significant impact on the recruitment of motor units and the rate of force development during contractions.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the mentioned study was the measure of muscle function in isolated muscle, which did not consider the critical physiological environment of the tissue, such as vascularization, oxygenation, and the contribution of the motor neuron and neuromuscular junction (NMJ) synaptic transmission, which might be affected by the presence of ethanol [ 87 ]. More recently, Laudato et al compared male and female mice for 1 h and 24 h after administering a binge-like dose of ethanol (5 g/kg) [ 25 ]. They used an in situ approximation, which better maintained the physiological muscle environment, and they found that both males and females exposed to binge ethanol exhibited a reduction in force production and enhanced muscle fatigue 1h after ethanol administration; however, only females recovered after 24 h of ethanol clearance, while males still presented some contractile deficits [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Laudato et al compared male and female mice for 1 h and 24 h after administering a binge-like dose of ethanol (5 g/kg) [ 25 ]. They used an in situ approximation, which better maintained the physiological muscle environment, and they found that both males and females exposed to binge ethanol exhibited a reduction in force production and enhanced muscle fatigue 1h after ethanol administration; however, only females recovered after 24 h of ethanol clearance, while males still presented some contractile deficits [ 25 ]. Nevertheless, and despite the possible differences between rats and mice, in both mentioned studies the binge protocol consisted of a single exposure, and contractile function was measured between 1 to 24 h after ethanol administration [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight, lean body mass, and skeletal muscle weight/whole body weight loss, as obvious markers of skeletal muscle atrophy, are commonly observed in models of alcohol-induced skeletal muscle atrophy [ 35 , 36 , 37 ]. Decreased muscle strength and increased perception of exercise fatigue have been reported in alcohol-fed mice [ 38 ]. In this experiment, zebrafish’s body weight, back muscle/body weight, and skeletal muscle fiber cross-sectional area were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%